2021
DOI: 10.1186/s12883-021-02063-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the CRS-R score on functional outcome in patients with severe brain injury receiving early rehabilitation

Abstract: Background The aim of the study was to determine the role of the Coma Recovery Scale-Revised (CRS-R) in the prediction of functional status at the end of neurological early rehabilitative treatment. Methods Patients consecutively admitted to intensive or intermediate care units of a neurological rehabilitation center were enrolled in the study. Consciousness and functional status were assessed with the Coma Recovery Scale-Revised (CRS-R) and the Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…These results confirm previous findings that MCS patients are more likely to recover within the first year after disease onset than patients in UWS, in particular when they improve to MCS within the first month [ 2 , 5 ]. While a previous study from our group has shown that initial CRS-R score as well gains after 4 weeks predicted outcome at the end of post-acute rehabilitation [ 12 ], these findings do not apply to the one-year outcome. Since a considerable number of patients regain minimal or full consciousness during post-acute rehabilitation, the final assessment of consciousness may have a higher predictive value for the long-term outcome than the initial assessment.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…These results confirm previous findings that MCS patients are more likely to recover within the first year after disease onset than patients in UWS, in particular when they improve to MCS within the first month [ 2 , 5 ]. While a previous study from our group has shown that initial CRS-R score as well gains after 4 weeks predicted outcome at the end of post-acute rehabilitation [ 12 ], these findings do not apply to the one-year outcome. Since a considerable number of patients regain minimal or full consciousness during post-acute rehabilitation, the final assessment of consciousness may have a higher predictive value for the long-term outcome than the initial assessment.…”
Section: Discussioncontrasting
confidence: 72%
“…Several studies, however, suggest that a considerable proportion of critically ill patients recover later, in particular during post-acute inpatient rehabilitation [ 6 8 ] or even years after the injury [ 9 11 ]. In a recent study investigating critically ill patients receiving post-acute rehabilitation, outcome at discharge was independently predicted by age, initial CRS-R score and gains in CRS-R score after 4 weeks [ 12 ]. The present study aims to extend previous findings by following up the outcome of these patients 1 year after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Studies [ 2 4 ] have found that organ failure and secondary infection after brain trauma are the most important causes of death. The literature reports [ 5 , 6 ] a fatality rate that can reach 50.17%, and the concurrent pulmonary infection rate can be as high as 60.84%. STBI patients are prone to secondary pulmonary infection, which can significantly increase the disability and mortality of patients [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the behavioral assessment of consciousness, the revised Coma Recovery Scale (CRS-R) is being applied in addition to clinical consensus as part of the clinical routine by trained staff, which is familiar with the CRS-R scoring system 36 , 37 . The CRS-R is an internationally accepted instrument for the monitoring of disorders of consciousness providing a rough estimate of the functional outcome as well 38 . The CRS-R encompasses six subscales that are each built in a hierarchical order with increasing scores indicating an increase in complexity of behavior.…”
Section: Methodsmentioning
confidence: 99%